(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Peritoneal tuberculosis can closely mimic ovarian cancer in its clinical and radiologic presentation, particularly in high-tuberculosis-burden regions, including Kenya. Early recognition is key to avoid misdiagnosis and inappropriate management. Case presentation: A 17-year-old presented with abdominal distension, pain, and unintentional weight loss. Imaging demonstrated bilateral complex ovarian masses, ascites, and peritoneal nodularity, with an elevated cancer antigen 125 (CA-125) level of 221 U/mL. Diagnostic laparoscopy revealed diffuse peritoneal tubercles, and biopsy confirmed granulomatous inflammation of peritoneal tissue with acid-fast bacilli consistent with peritoneal tuberculosis. The patient showed marked clinical and radiological improvement after six months of standard antituberculosis therapy. Conclusion: Peritoneal tuberculosis is an important differential diagnosis for ovarian cancer. In high-prevalence settings such as Kenya, clinicians must maintain a high index of suspicion when evaluating patients with features suggestive of ovarian cancer to facilitate timely diagnosis and appropriate referral. Keywords: CA-125, ovarian cancer, peritoneal tuberculosis.